Growth Retardation in Children with Kidney Disease - Paulina Salas; Viola Pinto; Josefina Rodriguez; Maria Jose Zambrano; Veronica Mericq (International Journal of Endocrinology)
Growth failure is almost inextricably linked with chronic kidney disease (CKD) and end-stage renal disease (ESRD). Growth failure in CKD has been associated with both increased morbidity and mortality. Growth failure in the setting of kidney disease is multifactorial and is related to poor nutritional status as well as comorbidities, such as anemia, bone and mineral disorders, and alterations in hormonal responses, as well as to aspects of treatment such as steroid exposure. This review covers updated management of growth failure in these children including adequate nutrition, treatment of metabolic alterations, and early administration of recombinant human growth hormone (GH).